Preceptors in Medical Residency Programs: Epidemiological Profile and Pedagogic Training - Carvalho Filho,Aderval de Melo (2020)
Abstract: Introduction: Medical Residency is a specialization course characterized as in-service training, considered in Brazil as the gold standard in the development of specialist physicians’ training. The medical residency preceptorship is an activity carried out by a specialist physician, responsible for monitoring resident physicians. However, there is neither a definition of the main requirements for such a preceptor, nor of his/her academic background to carry out the due teaching training, and it was possible to notice a relative lack of preparation regarding the pedagogical aspects. Methods: Descriptive study based on a quantitative approach, comprising 200 preceptors, of both genders, from medical residency programs in Maceió, state of Alagoas, Brazil. Results: The mean age was 43.31 ± 10.31 years, with a slight majority of female participants (52.5%). The mean time since graduation was 19.5 ± 10.58 years, and 83% of the participants had graduated in the state of Alagoas. Moreover, 78.5% said they had their Medical Residency certification, with an increased trend of public institution preceptors getting their degree at the stricto sensu level. The mean time of their completed postgraduate course was 12.63 ± 10.87 years and 7.07 ± 6.99 years being a preceptor. Only 19% mentioned they had some qualification for exercising the preceptorship, and 29.5% work as the teachers at the undergraduate level. The state of Alagoas has followed the expansion of the Residency programs, justifying the mean age found, similar to other studies. The majority of female participants can be associated with the feminization of health care professionals. The high percentage of preceptors with medical residency qualification is in accordance with Resolution n. 4/1978. We found experienced preceptors, but some authors differed. The low percentage of preceptors with qualification for exercising preceptorship indicates low interest and lack of available training. Conclusion: This study population is characterized as being young, and most are females. They have had long professional experience, and most have graduated in the state of Alagoas. There is a predominance of medical residency as their main qualification, and few of them have had training in the field. Finally, preceptors from public institutions have mostly got their degrees at the stricto sensu level.